Percutaneous Transluminal Angioscopy During Coronary Intervention. Issue 1 (2000) - Mizuno, Kyoichi; Sakai, Shunnta; Yokoyama, Shinnya; Ohba, Takayoshi; Uemura, Ryuta; Seimiya, Yasutsugu; Takano, Masamitsu; Tanabe, Jun; Tomimura, Masato; Imaizumi, Takahiro; Ma, Shu Mei; Inami, Shigenobu; et al.
Abstract : To investigate the feasibility of angioscopic-guided percutaneous transluminal coronary angioplasty and to elucidate the mechanism of efficacy of coronary stenting for acute myocardial infarction, we performed coronary angioscopy in 102 patients with stable angina or acute myocardial infarction. Thrombi and intimal flaps were observed in most patients after coronary angioplasty. Large intimal splits were seen in one third of patients. Stents were inserted in 10 patients who were revealed to have a large flap or protruding split to the inner lumen. Thrombolytic agents were administered in 2 patients with large thrombi. Additional treatments were required in 32% of patients. No acute myocardial infarction or unstable angina occurred in patients during hospitalization. Thus, angioscopy of the coronary lumen enables clinicians to determine the most appropriate and least risky coronary intervention strategy. In patients with acute myocardial infarction, angioscopy revealed occlusive or protruding thrombi in 34 of 35 patients. The protruding thrombi disappeared after stenting. The frequency of large intimal flaps increased after predilatation with balloon, but these disappeared after stenting. The present angioscopic study demonstrates that the coronary stent compresses the occlusive or protruding thrombi and covers the ruptured thrombogenic plaque Consequently, smooth-surfaced and wide vessel lumen are obtained.